A comprehensive assessment of a passive back support exoskeleton for load handling assistance - Jangwhan Ahn; Hyeonhee Jung; Jeongin Moon; Cheolmin Kwon; Jooeun Ahn (Scientific Reports)
Abstract Various back support exoskeletons (BSEs) have been developed to reduce the workload and the risk of musculoskeletal disorders. However, the evaluations of such devices have primarily focused on specific quantitative aspects like muscle activation level or metabolic cost without any assessment of the user perception or comfort. In addition, the absence of an universal guidance or agreement on the methods for quantifying the efficacy of exoskeletons has hampered a systematic comparison among the developed devices. This study introduces a newly developed passive BSE for heavy load handling workers, and verifies its assistive effect through a rigorous and multifaceted evaluation. Fifteen young and healthy males participated in two experiment sessions. In the first session, participants lifted a 15 kg box and held it in a static position. In the second session, participants performed repetitive lifting tasks with a 10 kg box. The developed BSE reduced root mean square, peak, and integrated muscle activation with statistical significance in the key muscles. The BSE alleviated muscle fatigue by delaying spectral shift of instantaneous median frequency in the lumbar erector spinae (p < 0.001) and gluteus maximus (p < 0.001). The BSE also decreased energy expenditure by 13.6% (p < 0.001). In addition, the BSE reduced participants’ rate of perceived exertion and local musculoskeletal discomfort by 14.7% (p = 0.005) and 30.5% (p = 0.001), respectively. These results support the efficacy of the developed BSE. The multifaceted evaluation process used in this study also contributes to proposing a systematic guidance on evaluating BSEs.